2021
DOI: 10.12998/wjcc.v9.i34.10494
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic segmentectomy and lobectomy assisted by three-dimensional computed-tomography bronchography and angiography for the treatment of primary lung cancer

Abstract: BACKGROUND Anatomical segmentectomy has been proposed as a substitution for lobectomy for early-stage lung cancer. However, it requires technical meticulousness due to the complex anatomical variations of segmental vessels and bronchi. AIM To assess the safety and feasibility of three-dimensional computed-tomography bronchography and angiography (3D-CTBA) in performing video-assisted thoracoscopic surgery (VATS) for lung cancers. METHODS In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…First, with the improvement in imaging technology and diagnostic level, the segmental vein can be clearly displayed. The operator can clarify the venous variation and its position relationship with the lesion through preoperative film reading, outline the boundary of the lesion through the segmental vein, and design the resection path of the internal edge of the lesion ( 16 , 17 ). Second, according to the traditional hilar approach, the vein is located in the deep surface of the artery and bronchus, which makes it difficult to expose it for dissection.…”
Section: Discussionmentioning
confidence: 99%
“…First, with the improvement in imaging technology and diagnostic level, the segmental vein can be clearly displayed. The operator can clarify the venous variation and its position relationship with the lesion through preoperative film reading, outline the boundary of the lesion through the segmental vein, and design the resection path of the internal edge of the lesion ( 16 , 17 ). Second, according to the traditional hilar approach, the vein is located in the deep surface of the artery and bronchus, which makes it difficult to expose it for dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Possible complications can also arise from variant anatomy: incorrect division of the intersegmental vein, or the accidental cutting of one of the veins supplying the bronchopulmonary segment, can cause postoperative hemoptysis [12,71,72]. Another example is confusion of the variant lingular segmental artery with an anterior segmental artery during a left upper or anterior segmentectomy [12].…”
Section: Table 2 Comparision Of Histological Diagnoses In Patients Un...mentioning
confidence: 99%
“…In a segmentectomy to treat cancer, the surgical margins should be extending at least 2 cm outside the lesion or should be 2 cm greater than the tumor size [12,18,72]. For this to be possible, the size of the segment should be taken into account.…”
Section: Table 2 Comparision Of Histological Diagnoses In Patients Un...mentioning
confidence: 99%
“…Iwano et al defined the virtual safety margin as a sphere extending 2 cm outside the tumor in preoperative 3D-CT simulation and reported that no positive surgical margin was achieved in all 17 primary lung cancers in 16 patients after segmentectomy [37]. Wu et al similarly reported 57 cases of VATS segmentectomy with preoperative 3D-CT simulation with a virtual 3D surgical margin defined as a sphere extending at least 2 cm outside the lesion or 2 cm greater than the tumor size and concluded that the combination of VATS and 3D-CT provided a transition from lesion-directed location of tumors to computeraided surgery for the management of early lung cancer [38]. Xu et al reported that 61 cases of u-VATS segmentectomy with intersegmental plane simulation by 3D reconstruction achieved a gross margin sufficiency of 100%, whereas 5 of 59 cases without intersegmental plane simulation did not achieve margin sufficiency [39].…”
Section: D-ct Simulation For Clinical Case Seriesmentioning
confidence: 99%